2014
DOI: 10.1128/jvi.01612-14
|View full text |Cite
|
Sign up to set email alerts
|

A Viral Protein Mediates Superinfection Exclusion at the Whole-Organism Level but Is Not Required for Exclusion at the Cellular Level

Abstract: Superinfection exclusion (SIE), the ability of an established virus infection to interfere with a secondary infection by the same or a closely related virus, has been described for different viruses, including important pathogens of humans, animals, and plants. Citrus tristeza virus (CTV), a positive-sense RNA virus, represents a valuable model system for studying SIE due to the existence of several phylogenetically distinct strains. Furthermore, CTV allows SIE to be examined at the whole-organism level. Previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 64 publications
0
66
1
Order By: Relevance
“…Our MOI estimate during cell-to-cell movement of TuMV (MOI of Ϸ30 genomes/cell) is much higher than those previously reported for any other virus (for a review, see reference 45), in particular for other plant RNA viruses, such as Tobacco mosaic virus (TMV) (29), Soilborne wheat mosaic virus (SBWMV) (30), Tobacco etch virus (TEV) (46), and Citrus tristeza virus (CTV) (32). The MOI ranges between 5 and 6 for SBWMV and between 1 and 2 for TMV, TEV, and CTV.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Our MOI estimate during cell-to-cell movement of TuMV (MOI of Ϸ30 genomes/cell) is much higher than those previously reported for any other virus (for a review, see reference 45), in particular for other plant RNA viruses, such as Tobacco mosaic virus (TMV) (29), Soilborne wheat mosaic virus (SBWMV) (30), Tobacco etch virus (TEV) (46), and Citrus tristeza virus (CTV) (32). The MOI ranges between 5 and 6 for SBWMV and between 1 and 2 for TMV, TEV, and CTV.…”
Section: Discussioncontrasting
confidence: 59%
“…Unfortunately, thus far, formally connecting these coinfection patterns to distinct MOIs is difficult due to the paucity of data. The MOI has been quantified in only a few multicellular host-virus models: an insect virus (27), an arbovirus in its mosquito vector (28), four plant viruses (each in a different host) (26,(29)(30)(31)(32), and HIV (33)(34)(35). In all cases the estimated values ranged from one to a few genome units per cell, suggesting that the MOI generally is low.…”
Section: Importancementioning
confidence: 99%
“…The corollary is that the MOI would be controlled at least in part by virus functions, and evidence derived mostly from the study of bacteriophages (31,(33)(34)(35) indicates that this is the case. Although it has been reported that the CTV-encoded protein p33 was required for superinfection exclusion at the plant and tissue level, it did not seem to have a role in MOI determination (23,28), and for plant viruses, there is no evidence of a role of viral functions in the control of the MOI.…”
Section: Discussionmentioning
confidence: 83%
“…Bergua et al (23) estimated the MOI in phloem-associated cells of young citrus trees that were infected with a variant of Citrus tristeza virus (CTV) (genus Closterovirus) and later superinfected with a second variant, with each CTV variant being tagged with two fluorescent proteins and both lacking the p33 protein. The MOI value was also low, ranging from 1.06 to 1.07 in different plant sections (23). Finally, Gutiérrez et al (24) obtained different estimates of the MOI at two phases of the systemic infection of a single systemically infected leaf of turnip plants by Turnip mosaic virus (TuMV).…”
mentioning
confidence: 99%
See 1 more Smart Citation